(untitled) (World Bulletin of Public Health, 2024)
The lumbar spine is the most frequently injured part of the spinal column. According to an epidemiological study in the United States in 2020, spinal injury was 253 per 1 million population, in Israel this figure was 370 people per 1 million inhabitants. Damage to the lumbar spine has an important social significance, representing a high percentage of disability and social maladjustment, to which young and working-age people are most susceptible